"Don't worry, it's reversible": fragmentation and subjectivity in art restoration ethics through a case study of Baumgartner fine art restoration - See Tow, Alexis York Ian (Nanyang Technological University, 2024)
This study examines the ethical considerations and implications of sensationalized art restoration practices, focusing on a critical analysis of the content produced by Baumgartner Fine Art Restoration, an independent studio. The research explores the tension between fundamental conservation principles and the content-driven approach of ASMR (Autonomous Sensory Meridian Response), a genre under which BFAR markets itself under. The primary objectives of this investigation are to scrutinize the implicit and explicit principles guiding BFAR's treatment processes and to evaluate their adherence to established ethical standards in the field. Furthermore, this paper posits that BFAR's approach is symptomatic of broader systemic issues within art restoration, including ethical subjectivities and unregulated practices, which are exacerbated by the fragmentation of the field. By elucidating these complex relationships, this paper places a reading on the pulse of the field of restoration by synthesising findings into a wider diagnostic evaluation of systemic issues surrounding the field of restoration itself, so as to incite a deep, comprehensive look into the negotiations of cultural heritage, ethics, authenticity, and the complexities of the art world.